T-regulatory cells for the treatment of autoimmune diseases - Fisher, Marina S.; Sennikov, Sergey V. (Frontiers in Immunology, 2025)
Autoimmune diseases result from imbalances in the immune system and disturbances in the mechanisms of immune tolerance. T-regulatory cells (Treg) are key factors in the formation of immune tolerance. Tregs modulate immune responses and repair processes, controlling the innate and adaptive immune system. The use of Tregs in the treatment of autoimmune diseases began with the manipulation of endogenous Tregs using immunomodulatory drugs. Then, a method of adoptive transfer of Tregs grown in vitro was developed. Adoptive transfer of Tregs includes polyclonal Tregs with non-specific effects and antigen-specific Tregs in the form of CAR-Treg and TCR-Treg. This review discusses non-specific and antigen-specific approaches to the use of Tregs, their advantages, disadvantages, gaps in development, and future prospects.